Pharmacogenetics of the prostaglandin-endoperoxide synthase 2 (PTGS-2) 5' and 3' untranslated regions in three distinct Asian populations. - Yip, Fong Ee. (2011)
Cyclooxygenase-2 (COX-2) is an enzyme induced in response to mitogens, tumour promoters, and cytokines. Gene expression of COX-2 is found to be upregulated in solid tumours. Polymorphisms in regulatory regions of PTGS-2 encoding COX-2 were demonstrated to influence COX-2 expression levels and alter risk association to various cancers, notably colorectal cancer.